Species composition and taxonomic status of bats in Eastern India (Zoological Records and Reviews, 2022)
Eastern India -- encompassing the states of West Bengal, Odisha, Jharkhand, and Bihar -- represents abiogeographically complex region at the confluence of the Indo-Gangetic Plain, the Eastern Ghats, and the transitionzone towards the northeastern Indian subregion. Despite this diversity, the chiropteran fauna of eastern India remainstaxonomically incomplete, with numerous nomenclatural issues unresolved and distributional data fragmented acrossscattered literature. This study presents a comprehensive species composition and taxonomic assessment of bats fromeastern India based on field surveys at 78 localities conducted between 2018 and 2021, supplemented by examination ofmuseum specimens and molecular analysis of mitochondrial cytochrome b sequences from 284 individuals. Wedocument 64 bat species belonging to 8 families and 32 genera, including 6 new state records and 2 candidate newspecies. The families Vespertilionidae (28 species) and Rhinolophidae (14 species) dominate the regional fauna.Molecular phylogenetic analysis resolves long-standing taxonomic uncertainty in the Rhinolophus trifoliatus complex andconfirms the species status of Kerivoula picta populations from Odisha forests, previously treated as conspecific withHimalayan populations. Updated echolocation parameters, morphometric diagnoses, and revised distribution maps areprovided for all documented species. Eighteen species are assessed as IUCN Threatened or Near Threatened. Roostsite loss, deforestation, and cave disturbance are identified as primary threats to bat conservation in eastern India.
Keywords: conservation; cytochrome b; Chiroptera; Eastern India; bat diversity; Vespertilionidae; Rhinolophidae; echolocation; taxonomic revision; new records